Development of Student Worksheets Assisted by Powtoon Media on Elasticity and Hooke's Law to Improve Student Learning Outcomes - Magrib, Yunisa Sy; Supartin; Jahja, Mohammad (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This research is a type of development research (Research and Development). with the aim of knowing the quality (Validity, Practicality, and effectiveness) of student worksheets assisted by Powtoon media on the material Elasticity and Hooke's Law. This research is a type of development research that refers to 4-D Model development research consisting of four development stages, namely Defining, Designing, Developing, and Disseminating. After being validated by 3 validators, a limited trial was carried out by 36 class XI participants at SMA Negeri 1 Kabila. Data collection techniques in this research used expert validation sheets, teacher and student response questionnaires, and student learning outcome tests. The research results show that validation is in the